PENERAPAN BALANCED SCORECARD SEBAGAI METODE PENGUKURAN KINERJA PADA RS IPHI PEDAN KABUPATEN KLATEN - Darmiyati, Jidanah; Purwanto, Agus (Diponegoro Journal of Accounting, 2013)
RS IPHI Pedan Klaten is one of the main referral hospital for the community. Fast service and the availability of adequate health is the reason the patient came to the hospital IPHI Pedan Klaten. Based on these phenomena is important for the performance measurement conduct business development strategies are suitable and can be used as a basis for repayment system. One method of performance measurement that takes into account financial and non-financial aspects are known as the Balanced Scorecard are applied in RS IPHI Pedan Klaten district in 2012. The problems described in this study are: 1) How does the performance of RS IPHI Pedan Klaten seen from a financial perspective, 2) How is the performance RS IPHI Pedan Klaten seen from the perspective of the customer, 3) How is the performance RS IPHI Pedan Klaten seen from the perspective of internal processes business, 4) How is the performance RS IPHI Pedan Klaten seen from the perspective of learning and growth.The design of this study used a descriptive quantitative approach. Data obtained from the results of the questionnaire and results documentation. Research subjects came from employees RS IPHI Pedan Klaten and RS patients IPHI Pedan KlatenPengujian research instruments used validity and reliability. Analysis using qualitative methods (for analysis not with numbers) and quantitative methods (for analysis using numbers).Based on the research that has been conducted, it was concluded that: for the financial perspective, RS IPHI P and Klaten produces performance can generally be said to be good for economic ratios, and efficiency ratios below 100% during the years 2010-2011, ie 42,97%; 41.19%; effectiveness ratio of 87,27% and above 10%. Customer perspective RS IPHI Pedan Klaten indicated satisfaction with the achievements of the percentage of patients achieving 55%, the percentage increased patient retention rate is 54,90%; 60.33%; 59.72%. Learning and growth perspective, RS IPHI Pedan Klaten shows the result of increased employee productivity for three consecutive years ie 2010, 2011, 2012 amounting to Rp. 13.763.472, Rp. 20.059.516, and Rp. 28.909.290. This increase is supported by the high level of employee satisfaction reached 50% and the employee retention rate is below 2% of total employees. RS IPHI Pedan Klaten district must maintain the achievement of the performance with some suggestions and improvements that need to be done.